5PSQ-004 Adequacy of antiemetic treatment during chemotherapy in a regional hospital. (24th March 2020) - Salom, C; Galceran, MDLE; Serrais, J; Retamero, A; Parés, RM; Sànchez, X; Medina, M; Roch, MÀ; Ferràndez, D
Abstract : Background and importance: Despite the availability of international guidelines for antiemetic treatment in chemotherapy, their implementation during daily clinical practice is not optimal. Aim and objectives: To assess adaptation of the antiemetic pattern to the degree of chemotherapy emetogenicity in a regional hospital, according to the clinical practice guidelines of MASCC/ESMO, ASCO and NCCN. Material and methods: A longitudinal retrospective study was conducted for population characterisation and non-intervention. Patients receiving intravenous chemotherapeutic treatment from April to July 2018 were included. Demographic variables (age and sex), indication for chemotherapy, scheme, cycle, administration of 5-HT3 antagonists, NK1 R antagonists, dexamethasone, and other antiemetics, and adaptation of the antiemetic treatment to guidelines were collected. Data are expressed by mean (SD) for continuous variables and by absolute and relative frequency for categorical variables. Statistical analysis was performed with R software (V.3.4.3). Results: The sample included 133 patients, aged 62.26 (11.13) years and 70 (52.63%) were women. They received chemotherapy for 12 different indications, with 45 different schemes, 66.92% undergoing their first cycle, and 33.08% their second or later. No patient was included at different cycles of his/her treatment. On the day of chemotherapy, 121 (90.98%) patients received antiemetic monotherapy or polytherapy. A total of 112 (84.21%) patients received a 5-HT3 antagonist, 69 (51.88%) an NK1 R antagonist and 112 (84.21%) dexamethasone. In the following days, 58 (43.61%) patients received monotherapy or polytherapy. Mainly, 34 (25.56%) were given dexamethasone, 10 (7.52%) a metoclopramide fixed schedule, 5 (3.76%) metoclopramide on demand and 5 (3.76%) a 5-HT3 antagonist. Adequacy of the recommendations of the guidelines was sufficient in 75 (56.39%) patients, while the remaining presented an excessive pattern (38 (28.57%) patients) or insufficient pattern (20 (15.04%) patients). The proportion of sufficient adequacy in the hospital population was estimated at 0.56 (0.47–0.64). Conclusion and relevance: Only slightly more than half of the patients received an antiemetic pattern in accordance with the internationally agreed clinical guidelines, so there is ample room for improvement. Among those with a non-consistent pattern, an excessive pattern was much more frequent. References and/or acknowledgements: No conflict of interest.